Do rare earths drive volatility spillover in crude oil, renewable energy, and high-technology markets? — A wavelet-based BEKK- GARCH-X approach. (15th July 2022) - Zheng, Biao; Zhang, Yuquan W.; Qu, Fang; Geng, Yong; Yu, Haishan
Abstract: Amidst the background of an increasingly evidenced shift to renewable energy, many studies explored the relationships between crude oil, renewable energy, and technology stock markets worldwide. However, research has yet to take the raw materials market into account financially. This study investigates the volatility spillovers between crude oil, renewable energy, and high-technology markets in China in time and frequency domains first. Thereupon the tri-market system gets expanded to include the raw materials market (rare earths). The framework of wavelet analysis and BEKK-GARCH model with exogenous variables is applied. The results corroborate that there exists significant volatility spillover between renewable energy and high-technology stock markets, and the renewable energy market in China relates closer to high-technology than crude oil. Besides, the volatility spillovers vary by frequency, with D 3 (8–16 days) results appearing more pronounced. Moreover, the rare earths market has significant impacts on the system, especially for high-technology and renewable energy markets. This suggests that as key raw materials to renewable energy development, rare earths may increase the risk transfer of the tri-market system. The results are of potential importance and use for investors and policy makers. In particular, taking the frequency perspective helps devising differentiated portfolio and risk management strategies. Highlights: The system of crude oil, renewable energy, and high-tech in China is explored. Renewable energy is closer with high-tech than with crude oil. The volatility spillovers of differentiated frequencies vary. The exogenous rare earths may increase the risk transfer of the system.